Epidemiology and risk factors for diverticular disease - Violi, Alessandra; Cambiè, Ginevra; Miraglia, Chiara; Barchi, Alberto; Nouvenne, Antonio; Capasso, Mario; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Diverticulosis of the colon is the most frequent anatomical alteration diagnosed at colonoscopy. The prevalence of the disease is higher in elderly patients over 65 years old, recent studies show an increment also in youngers over 40 years old. Even its large prevalence in the population, its pathophysiology still remain poorly understood. It’s widely accepted that diverticula are likely to be the result of complex interactions among genetic factors, alteration of colonic motility, lifestyle conditions such as smoking, obesity, alcohol consumption, fiber and meat intake with diet. Recently many authors considered also alterations in colonic microbiota composition, co-morbidity with diabetes and hypertension and the chronic assumption of certain medications like PPI, ARB and aspirin, as important risk factors for the development of diverticulosis. The aim of this narrative review is to summarise current knowledges on this topic.